The missions of Jesus and the disciples according to the fourth gospel. With implications for the fourth gospel's purpose and the mission of the contemporary church - DF Tolmie (Acta Theologica)
This book is a revision of Köstenberger's doctoral dissertation, completed in 1993 under Prof. D.A. Carson at Trinity Evangelical Divinity School.